Error Analysis in Writing Chinese Essay: A Case Study of Chinese Major Students of UBRU - Songsukrujiroad, Sappasiri; Chen, Xin; Kaewyod, Wisuda (International Journal of Integrated Education and Development, 2018)
In this research study, the researcher attempted to indicate errors in Chinese writing skills made by 25 third year Chinese major students of UBRU during the 2017 academic year in order to improve the ability of Chinese writing. The instrumentIn this research study, the researcher attempted to indicate errors in Chinese writing skills made by 25 third year Chinese major students of UBRU during the 2017 academic year in order to improve the ability of Chinese writing. The instrumentof this study was an essay--a set topic for free writing, ‘My Future Career’ (我未来的事业). These third year Chinese major students were assigned to write this essay of at least 350 Chinese characters within 30 minutes. All of the errors taken from data collection were analyzed, identified and classified into various categorizations. After data analysis, the results of the study indicated that most students had six errors on Chinese writing: 1) word choice, 2) word order, 3) punctuation, 4) wrong Chinese character, 5) conjunction, and 6) classifier. This study has enhanced on the manner in which students can be internalized the rules of targeted language, which is Chinese. The results of this study provided information on common trouble-spots in Chinese language learning which can be used in the preparation of effective teaching materials.